GAMBARAN PEMERIKSAAN INSPEKSI VISUAL ASETAT SEBAGAI DETEKSI LESI PRAKANKER SERVIKS PADA WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT X KECAMATAN PAYUNG SEKAKI PEKANBARU - Monaliza "; Wiwit Ade Fidiawati; Amru Sofian (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is a malignancy in the cervix who occupy the highest rank as the most common disease in women in the world. This disease can be detected earlier with Visual Inspection with Acetic Acid (VIA) examination. This paper describes an overview of VIA as the detection of cervical precancerous lesions in the indirect Female Sex Workers (FSW) at hotspot X District Payung Sekaki Pekanbaru. This disease can be detected early with inspection Visual Inspection Acetate (VIA) is a simple examination with the outward appearance of 3-5% acetic acid on the cervix. This study aims to clarify the picture VIA examination as the detection of precancerous cervical lesions and determine the characteristics of the indirect Female Sex Workers (FSW) at hotspot X District Payung Sekaki Pekanbaru. The method used is descriptive observational. Population of research are all in the indirect Female Sex Workers (FSW) at hotspot X District Payung Sekaki Pekanbaru and samples were taken using total sampling. Results of this study found respondents with positive results VIA (acethowhite) as many as 14 people (45.16%). The conclusion from this study is that the majority of indirect Female Sex Workers (FSW) at hotspot X have tested negative VIA.Key words : VIA, Cervical cancer, Indirect Female Sex Workers, Hotspot X